Using formative assessment to support student learning objectives - Schneider, M. Christina; Johnson, Robert L. 1958- (Student assessment for educators, 2019)
"As student learning objectives become an increasingly prominent approach to setting goals and growth measures in schools, teachers' competence in formative assessment is essential. Using Formative Assessment to Support Student Learning Objectives introduces current and future educators to SLOs as tools for shaping career- and college-ready students. Written in concise and straightforward language, and replete with step-by-step exercises, real-life examples, and illustrative charts, this useful guide provides pre- and in-service educators with the theoretical background and practical tools needed to implement the latest SLO research in their classrooms"--